Boardroom integrity and the crusade against fraud: Navigating corporate governance in Indonesia - Juhandi, Nendi (Privietlab, 2022)
This study delves into the intricate landscape of corporate governance within Indonesian corporations, scrutinizing its efficacy in deterring financial statement fraud. By amalgamating insights from a systematic literature review, quantitative analyses of secondary data, and logistic regression methods, the research elucidates the multifaceted interplay between various governance mechanisms and the persistence of fraudulent activities. Central to our findings is the pivotal role of board size in enhancing corporate oversight and mitigating fraud, juxtaposed against the ambiguous impacts of other governance elements such as audit committee effectiveness and board experience. This complexity underscores the paramount importance of ethical leadership and the